(untitled) (Italian Journal of Public Health, 2008)
Background: Orthodontic Treatment Need Indexes are investigated to evaluate their validity criteria and their formulation on a scientific basis. Methods: A bibliographic research was performed on Medline Database to find articles about orthodontic treatment need indexes published from 1960 to 2007. English language papers about criteria to establish indexes, their validity and reproducibility, and comparing two or more indexes were chosen. Results: The study shows that orthodontic treatment need indexes are not based on evidence but are all based on the opinion of experts, although widely shared by the orthodontic community since the use of these indexes in clinical practice. The validity is assessed in terms of objectivity of the measurements needed to evaluate the clinical severity of the case under consideration. In this case, the quantitative methods seem to be more reliable and objective than the qualitative. Conclusions: Currently in the orthodontic field the theory that orthodontic therapy is useful to prevent any disease in the patients is not supported by evidence based medicine. The recommendations about orthodontic treatment need should come from scientific debates, in order to support consensus based decisions.